Treatment of venous leg ulcers with sulodexide - Kucharzewski, M.; Franek, A.; Koziolek, H. (Phlebologie, 2003)
Aim: The study of the influence of sulodexide in the treatment of venous leg ulcers. Patients and method: 44 patients with chronic venous ulceration were randomly divided into two groups. Group I: 21 patients (ulceration area: 12.7-18.9 cm2), Group II: 23 patients (ulceration size: 12.1-20.3 cm2). Both groups were treated by using Unna’s boot. This dressing was changed every seven days until the ulcer had healed. Additionally, the patients in group II received the systemic pharmacological treatment with sulodexide. Results: After 7 weeks of treatment ulcers of seven patients (35%) from group I had healed, and 3 weeks later the ulceration of two more patients had healed completely. After further 7 weeks the ulcers of 12 patients had healed completely. Whereas in group II after 7 weeks of treatment ulceration of 16 (70%, p <0.05) patient had healed completely and after further 3 weeks the ulcers of the remaining 7 patients had healed, too. Conclusion: The use of sulodexide in patients with chronic venous leg ulcers accelerates the healing process.
Keywords: Sulodexide; venous leg ulcers